2012
DOI: 10.1155/2012/795452
|View full text |Cite
|
Sign up to set email alerts
|

Beneficial Effects of Long-Term Administration of an Oral Formulation of Angiotensin-(1–7) in Infarcted Rats

Abstract: In this study was evaluated the chronic cardiac effects of a formulation developed by including angiotensin(Ang)-(1–7) in hydroxypropyl β-cyclodextrin (HPβCD), in infarcted rats. Myocardial infarction (MI) was induced by left coronary artery occlusion. HPβCD/Ang-(1–7) was administered for 60 days (76 μg/Kg/once a day/gavage) starting immediately before infarction. Echocardiography was utilized to evaluate usual cardiac parameters, and radial strain method was used to analyze the velocity and displacement of my… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
38
1
2

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(44 citation statements)
references
References 45 publications
3
38
1
2
Order By: Relevance
“…Taking advantage of this formulation, Marques et al (2011Marques et al ( , 2012 found that chronic oral administration of HPbCD/Ang-(1-7) significantly attenuated the impairment of heart function and cardiac remodeling induced by isoproterenol treatment and myocardial infarction in rats. Furthermore, CGEN-856S, a Mas agonist, promoted antiarrhythmic effects and produced a small dosedependent decrease in arterial pressure in conscious SHR (Savergnini et al 2010).…”
Section: Figurementioning
confidence: 99%
“…Taking advantage of this formulation, Marques et al (2011Marques et al ( , 2012 found that chronic oral administration of HPbCD/Ang-(1-7) significantly attenuated the impairment of heart function and cardiac remodeling induced by isoproterenol treatment and myocardial infarction in rats. Furthermore, CGEN-856S, a Mas agonist, promoted antiarrhythmic effects and produced a small dosedependent decrease in arterial pressure in conscious SHR (Savergnini et al 2010).…”
Section: Figurementioning
confidence: 99%
“…59,60 These studies were limited in scope, and native Ang(1-7) has not been developed further because of its abbreviated half-life in vivo. A cyclic Ang(1-7) analog containing a thioether bridge that makes it resistant to enzymatic digestion and a hydroxypropyl-β-cyclodextrin incorporated Ang(1-7) formulation (HP-β-CD/Ang1-7) have been synthesized and shown to be cardioprotective in animal models of myocardial infarction and insulin resistance/type 2 diabetes [61][62][63] (Table). As an alternative to Ang(1-7), nonpeptide agonists of the Mas receptor, for example, the imidazole compound AVE0991, 64 and novel G-protein-coupled receptor activating peptides, for example, CGEN-856S that have high specificity for the Mas receptor, 65 have been shown to lower BP and protect the vasculature and kidneys in animal models of hypertension and CVD (Table).…”
Section: Activators Of the Angiotensin-converting Enzyme2/angiotensinmentioning
confidence: 99%
“…The fact that LVH is an independent risk factor for the development of HF reinforces the importance of this finding. In addition, others 7,8,21 have demonstrated that Ang-(1-7) prevents extracellular matrix deposition, a key event in the transition from LVH to symptomatic HF that may also contribute to Ang-(1-7) protection in TG-DOCA.…”
Section: Discussionmentioning
confidence: 99%